(untitled) (The East and Central African Journal of Pharmaceutical Sciences, 2018)
Indomethacin in ground pellet mixture was fed to a group of starved albino mice 6-8 weeks old, weighing 20-26 g in varying concentrations ranging from 0.0125–1.0 % w/w. The mice were observed for signs of toxicity over a period of 8 days or until death and the LD100 determined. The same LD100 indomethacin concentration was fed to a group of albino rats to determine if the results could be replicated in a different rodent species. All the mice fed concentrations of indomethacin ranging from 0.0625–1.0% died within 3 days and none died within 24 h. These results were replicated in rats but in this case, death occurred within 6 days. The LD100 indomethacin dose in mice was 35 mg/kg body weight compared to 65mg/kg given in literature for Zinc Phosphide. Most prominent manifestation of toxicity at death was extensive haemorrhage in gastrointestinal tract. Blood clotting time just before death was over 30 minutes compared to that of control mice which was 10-15 sec. Zinc phosphide, flocoumafen, difethiolone and bromadiolone, all established rodenticides in the Kenya market were fed to mice for purposes of comparison and their rodenticidal effects confirmed. On the basis of these results use of indomethacin as rodenticide is justified as it is much cheaper, readily available and safer in humans compared to other rodenticides in the market